The Influence of Transparency and Community Participation on the Effectiveness of Public Services Through the Satisfaction of the Deli Tua Sub-District Community - Zega, Seplin Bin Lan Jaya; Parinduri, Ramadha Yanti; Zsasa, Cut Sah Kha Mei (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The effectiveness of public services at the local government level is often constrained by limited transparency and low community participation, which in turn affects public satisfaction. This study aims to examine the effects of transparency and community participation on public service effectiveness, with community satisfaction serving as a mediating variable, in Deli Tua Subdistrict. The study is grounded in theories of governmental transparency, public participation, and community satisfaction within public administration. A quantitative survey method was employed involving 99 respondents, with data analyzed using t-tests and path analysis. The results indicate that transparency and community participation have positive and significant effects on community satisfaction and public service effectiveness, both directly and indirectly. These findings highlight that improving public service effectiveness requires not only procedural efficiency but also enhanced information openness and active citizen involvement in service delivery.